2015
DOI: 10.7476/9788579836626
|View full text |Cite
|
Sign up to set email alerts
|

A problematização em educação em saúde: percepções dos professores tutores e alunos

Abstract: Todo o conteúdo deste trabalho, exceto quando houver ressalva, é publicado sob a licença Creative Commons Atribição 4.0.Todo el contenido de esta obra, excepto donde se indique lo contrario, está bajo licencia de la licencia Creative Commons Reconocimento 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 44 publications
0
9
0
34
Order By: Relevance
“…Another study showed that, through the activities developed with communities in the set of subjects, students could understand the power of education as a social transformation tool, and recognize the tensions resulting from dealing with problematizing teaching practices. The investigation highlighted the presence of constructive and questioning dialogues among the people involved and the bet in transformative actions 7 .…”
Section: Study In Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that, through the activities developed with communities in the set of subjects, students could understand the power of education as a social transformation tool, and recognize the tensions resulting from dealing with problematizing teaching practices. The investigation highlighted the presence of constructive and questioning dialogues among the people involved and the bet in transformative actions 7 .…”
Section: Study In Progressmentioning
confidence: 99%
“…[...] awareness of the importance of health education and the different forms and situations in which it can be carried out7 . (p. 79) [...] I think it is necessary to discuss health education.…”
mentioning
confidence: 99%
“…Falar de currículo e de aproximação entre o mundo escolar e o mundo do trabalho, como propõem as políticas de flexibilização da pós-graduação, nos traz à memória a importância de termos na realidade concreta extraescolar o referencial para a seleção, desenvolvimento e aplicação de conteúdos (FREIRE, 1987), bem como nos remete aos debates sobre o tradicionalismo pedagógico característico de nossas universidades (BORDENAVE;PEREIRA, 1983;ALMEIDA FILHO, 2011;VILLARDI;BERBEL, 2014) e sobre o não resolvido dilema, já trazido por Saviani (1981), entre a pedagogia tradicional e as tendências pedagógicas derivadas do escolanovismo (LIBÂNEO, 1985). Nesse sentido, a construção adequada de objetivos educacionais teoricamente fundamentados é um importante passo, pois nos permite orientar a prática pedagógica segundo pressupostos teóricos claros, identificar pontos de chegada e analisar resultados, avaliando sua eficácia e efetividade.…”
Section: Considerações Finaisunclassified
“…Concomitantemente, a pesquisa também demonstrou que a abordagem da subunidade também produz impactos positivos o que é corroborado por Villardi, Cyrino e Berbel (2011) [16], Prado et al (2012) [13] e Maia (2014) [9].…”
Section: Figura 2 Gráfico Comparativo Com a Quantidade De Entrevistadosunclassified